CHAPTER 23 HEAVY-MINERAL PROVENANCE IN AN ESTUARINE ENVIRONMENT, WILLAPA BAY, WASHINGTON, USA: PALAEOGEOGRAPHIC IMPLICATIONS AND ESTUARINE EVOLUTION - Bynum G.L. (My University, 2007)
Modern sediments from representative localities in Willapa Bay, Washington, comprise two principal heavy-mineral suites. One contains approximately equivalent amounts of hornblende, orthopyroxene, and clinopyroxene; this is derived from the Columbia River, which discharges into the Pacific Ocean a short distance south of the bay. The other suite, dominated by clinopyroxene, is restricted to sands of rivers flowing into the bay from the east. The heavy-mineral distributions within the bay suggest that sand discharged from the Columbia River, borne north by longshore transport and carried into the bay by tidal currents, accounts for nearly all of the sand within the interior of Willapa Bay today. Pleistocene deposits on the east side of the bay contain three heavy-mineral assemblages, two of which are identical to the modern assemblages described above. These assemblages reflect the relative influence of tidal and fluvial processes on the Late Pleistocene deposits (100,000-200,000 BP. Amino acid racemization in Quaternary shell deposits at Willapa Bay, Washington. Geochimica et Cosmochimica Acta 43, 1505-1520). They are also consistent with those processes inferred on the basis of sedimentary structures and stratigraphic relations in about two-thirds of the samples examined. Anomalies can be explained by recycling of sand from older deposits. The persistence of the two heavy-mineral suites suggests that the pattern of estuarine sedimentation in Late Pleistocene deposits closely resembled that of the modern bay. The third heavy-mineral suite is enriched in epidote and occurs in a few older Pleistocene units. On the north side of the bay, the association of this suite with southwest-directed foresets in cross-bedded gravel indicates derivation from the northeast, perhaps from an area of glacial outwash. The presence of this suite in ancient estuarine sands exposed on the northeast side of the bay suggests that input from this northerly source may have intermittently dominated Willapa Bay deposition in the past. © 2007 Elsevier B.V. All rights reserved.
Keywords: COLUMBIA RIVER; ESTUARINE; FLUVIAL; HEAVY-MINERAL PROVENANCE; PALAEOGEOGRAPHY; PLEISTOCENE; WASHINGTON; Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная::Плейстоцен